A review on flow characterization methods for cereal grain‐based powders. (1st July 2015) - Ambrose, RP Kingsly; Jan, Shumaila; Siliveru, Kaliramesh
Abstract: Flow difficulties during handling, storage, and processing are common in cereal grain‐based powder industries. The many studies that focus on the flow properties of powders can be classified as flow indicators, shear properties, and dynamic flow properties. The non‐uniformity of physical and chemical characteristics of the individual particles that make up the bulk solid of cereal grain‐based powders adds complexity to the characterization of flow behavior. Even so, knowledge of flow behavior is critical to the design of productive and cost‐effective equipment for handling and processing of these powders. Because many factors influence flow, a single property/index value may not satisfactorily quantify the flow or no‐flow of powders. For powders of biological origin, chemical composition and environmental factors such as temperature and relative humidity complicate flow characterization. This review focuses on the specific flow characteristics that directly affect powder flow during handling, processing, and storage. © 2015 Society of Chemical Industry